2019
DOI: 10.1097/oi9.0000000000000024
|View full text |Cite
|
Sign up to set email alerts
|

Satisfactory postoperative alignment following retrograde SIGN Fin nailing for femoral shaft fractures

Abstract: Purpose: In developing countries, long bone fractures following trauma are a significant contributor to morbidity, and operating room resources are often limited in these settings. The Surgical Implant Generation Network (SIGN) Fin nail may reduce the challenges of retrograde intramedullary nailing of femoral fractures without fluoroscopy. In contrast to the traditional SIGN nail placed in a retrograde fashion, the Fin nail does not require proximal interlocking screws. Instead, the nail achieves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…On immediate postoperative radiographs, the authors found no difference in overall alignment or rates of malalignment >5° between groups. [ 16 ] The current study builds upon this previous work by examining postoperative radiographic alignment at a minimum of 6 months following surgical fixation. The relatively low rate of malalignment >10° in any plane (6%) suggests that the SIGN Fin nail is able to successfully maintain satisfactory fracture alignment for a minimum of 6 months, at which time most femoral shaft fractures have healed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On immediate postoperative radiographs, the authors found no difference in overall alignment or rates of malalignment >5° between groups. [ 16 ] The current study builds upon this previous work by examining postoperative radiographic alignment at a minimum of 6 months following surgical fixation. The relatively low rate of malalignment >10° in any plane (6%) suggests that the SIGN Fin nail is able to successfully maintain satisfactory fracture alignment for a minimum of 6 months, at which time most femoral shaft fractures have healed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the immediate postoperative alignment achieved by the Fin nail when used in the retrograde treatment of femoral shaft fractures in adults. [ 16 , 17 ] To our knowledge, however, no large study has investigated the long term clinical and radiographic performance of the SIGN Fin nail when used in this fashion. The purpose of this study is to examine long term clinical and radiographic outcomes in a large series of femoral shaft fractures treated with the SIGN Fin nail (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture alignment was measuring using degrees of DFAA, and measurements were made utilizing an on screen protractor tool (Screen Protractor; Iconico Inc, New York, New York) as previously described. [7,8] which was layered over films from the database (Fig. 2).…”
Section: Fracture Alignment Measurements and Classificationmentioning
confidence: 99%
“…Although there is a growing body of evidence supporting the use of the SIGN FIN nail for femoral fractures, there is no evidence of the use of SIGN FIN nail for treatment of tibial fractures. 13–15…”
Section: Introductionmentioning
confidence: 99%
“…10 Although there is a growing body of evidence supporting the use of the SIGN FIN nail for femoral fractures, there is no evidence of the use of SIGN FIN nail for treatment of tibial fractures. [13][14][15] In this study, we report outcomes with SIGN FIN nailing of tibial fractures to compare with those performed with the standard SIGN tibial nail or other locked intramedullary nails and to determine whether there are increased complications in the SIGN FIN group. We used the SIGN FIN nail because of a shortage of standard locked nails in our setup.…”
Section: Introductionmentioning
confidence: 99%